2007
DOI: 10.1080/01904160701289974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc × Boron Interaction on Plant Growth and Tissue Nutrient Concentration of Corn

Abstract: A pot experiment was conducted in a greenhouse on a calcareous soil (fine, mixed, mesic, Fluventic Haploxerepts) to study the interaction of zinc (Zn) and boron (B) on the growth and nutrient concentration of corn (Zea mays L.). Treatments consisted of a factorial arrangement of seven levels of B (0, 2.5, 5, 10, 20, 40, and 80 mg kg −1 as boric acid), two sources of Zn [zinc sulfate (ZnSO 4 · 7H 2 O) and zinc oxide (ZnO)], and three levels of Zn (0, 5, and 10 mg kg −1 ) in a completely randomized design with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 17 publications
5
27
0
5
Order By: Relevance
“…Ohse (2000), in his work, noticed a possible antagonistic effect between Zn and B, as well as between B and Cu; however, Hosseini et al (2007) reported a significant interaction between B and Zn on corn plants growth, with a synergetic effect among these nutrients. Lefebre et al (2002) On the basis of the levels of B and Zn on the aerial part of the plants, the minimum level was 137.85 and 98.2 mg.kg-¹ and the maximum was of 204.40 and 418 mg.kg-¹, respectively ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Ohse (2000), in his work, noticed a possible antagonistic effect between Zn and B, as well as between B and Cu; however, Hosseini et al (2007) reported a significant interaction between B and Zn on corn plants growth, with a synergetic effect among these nutrients. Lefebre et al (2002) On the basis of the levels of B and Zn on the aerial part of the plants, the minimum level was 137.85 and 98.2 mg.kg-¹ and the maximum was of 204.40 and 418 mg.kg-¹, respectively ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…There were low significant interactions between the micronutrient applications. The interaction between Zn and B on plant growth, when the availability of Zn and B is low, has also been documented in other crops (Hosseini et al, 2007). According to Bozoglu et al (2007) on neutral pH soil, the Zn × Mo interaction on the chickpea growth was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…A interação B e Zn foi claramente comprovada por Hosseini et al (2007), através da demonstração desses elementos em numerosos processos bioquímicos e fisiológicos em plantas de milho. As interações nutricionais interferem na composição mineral da planta podendo um elemento estimular ou inibir a absorção de outros elementos.…”
Section: Introductionunclassified